ACMEOLOGICAL ASPECT OF MODULE ENVIRONMENT OF UNIVERSITY - Богославець, Л. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article analyzes the interaction of the main components of the akmeological environment of the university, its role in the process of formation and further growth of the professional level of the teacher. The purpose of the rating system and feedbacks for improving the professional skills of the scientific and pedagogical staff of the university is being clarified